2009
DOI: 10.1111/j.1600-0781.2009.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrowband UVB treatment of pigmented purpuric lichenoid dermatitis (Gougerot–Blum)

Abstract: Summary Pigmented purpuric dermatoses are a group of dermatoses characterized clinically by pinpoint petechia and purpura on a brown, red or yellow base. Five diseases are included in the group of pigmented purpuric eruptions which significantly overlap clinically and histologically. Phototherapy in various forms of purpuric dermatoses has been reported in literature previously. Here we present a case of pigmented purpuric lichenoid dermatitis which rapidly cleared with narrowband UVB therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 6 publications
0
19
0
3
Order By: Relevance
“…PPDs are divided into five clinical groups, including progressive PPD (Schamberg's disease), purpura The etiology of the disease is still unknown. The postulated etiological factors include gravity and increased venous pressure, capillary fragility, exercise, focal infections, chemical foods, medications, contact with aniline paints, and alcohol consumption (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…PPDs are divided into five clinical groups, including progressive PPD (Schamberg's disease), purpura The etiology of the disease is still unknown. The postulated etiological factors include gravity and increased venous pressure, capillary fragility, exercise, focal infections, chemical foods, medications, contact with aniline paints, and alcohol consumption (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…However, with further reduction of the frequency of NB UVB the lesions flared. 17 Kocaturk et al 2 reported a case of pigmented purpuric lichenoid dermatitis that improved markedly with 20 treatments of NB UVB followed by another 10 sessions of light therapy, given as a maintenance therapy with total cumulative dose of 27 J ⁄ cm 2 . To the best of our knowledge, there is no previous report indicating treatment of Majocchi's purpura with light therapy.…”
Section: Nb Uvb In Pigmented Purpuric Dermatosesmentioning
confidence: 99%
“… 6 Kocaturk et al reported a case of pigmented purpuric lichenoid dermatitis that improved markedly with 20 NB-UVB treatments, followed by another 10 maintenance sessions with a total cumulative dose of 27 J/cm². 7 …”
Section: Discussionmentioning
confidence: 99%